2016
DOI: 10.1093/mnras/stw2070
|View full text |Cite
|
Sign up to set email alerts
|

Cosmology constraints from shear peak statistics in Dark Energy Survey Science Verification data

Abstract: Shear peak statistics has gained a lot of attention recently as a practical alternative to the two point statistics for constraining cosmological parameters. We perform a shear peak statistics analysis of the Dark Energy Survey (DES) Science Verification (SV) data, using weak gravitational lensing measurements from a 139 deg 2 field. We measure the abundance of peaks identified in aperture mass maps, as a function of their signal-to-noise ratio, in the signal-to-noise range 0 ă S{N ă 4. To predict the peak cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
148
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(158 citation statements)
references
References 113 publications
(94 reference statements)
10
148
0
Order By: Relevance
“…The same is true for other large-scale structure probes not shown in Fig. 4 such as the CFHTlens weak lensing shear survey (Heymans et al 2013), the peak statistics of lensing (Liu et al 2015;Kacprzak et al 2016), or the Sunyaev-Zeldovich cluster counts (Ade et al 2016). The contours from Planck15 (Ade et al 2015), on the other hand, do not agree with the observed velocity function at the 2-σ level.…”
Section: Cosmological Parameter Estimationmentioning
confidence: 70%
“…The same is true for other large-scale structure probes not shown in Fig. 4 such as the CFHTlens weak lensing shear survey (Heymans et al 2013), the peak statistics of lensing (Liu et al 2015;Kacprzak et al 2016), or the Sunyaev-Zeldovich cluster counts (Ade et al 2016). The contours from Planck15 (Ade et al 2015), on the other hand, do not agree with the observed velocity function at the 2-σ level.…”
Section: Cosmological Parameter Estimationmentioning
confidence: 70%
“…WL peaks, on the other hand, are high signal regions, that are closely associated with massive structures along the line-of-sight (LOS). Their statistics is a simple and effective way to capture the non-Gaussian information in the WL field, and thus highly complementary to the cosmic shear 2PCF (e.g., Kruse & Schneider 1999;Dietrich & Hartlap 2010;Shan et al 2012Shan et al , 2014Marian et al 2012Marian et al , 2013Lin & Kilbinger 2015;Martinet et al 2015;Hamana et al 2015;Liu et al, 2015aLiu et al, , b, 2016Kacprzak et al 2016).…”
mentioning
confidence: 99%
“…With the same method, Liu et al (2016b) presented constraints on the f(R) theory with the CFHTLenS data. Kacprzak et al (2016) measured the shear peaks using aperture mass maps (Schneider 1996;Bartelmann & Schneider 2001) from the Dark Energy Survey Science Verification (DES-SV) data. To derive cosmological constraints, they also adopted the simulation approach to produce WL maps (Dietrich & Hartlap 2010) spanning the (Ωm, σ8) plane.…”
mentioning
confidence: 99%
“…These include the lack of halo clustering, inaccurate modelling of the halo concentration, and the use of NFW profiles. Kacprzak et al (2016) have also argued that ignoring source clustering results is a boost factor to peak counts. See also the discussion in Sect.…”
Section: Parameter Constraints From Peak Countsmentioning
confidence: 99%
“…Since then, many other papers have explored the efficacy of peaks for constraining both standard and nonstandard cosmological models (Marian et al 2009(Marian et al , 2011(Marian et al , 2012(Marian et al , 2013Dietrich & Hartlap 2010;Maturi et al 2010Maturi et al , 2011Pires et al 2012;Cardone et al 2013;Lin & Kilbinger 2015a,b;Lin et al 2016). Regarding recent surveys, peak analyses have also been used to derive constraints on (σ 8 , Ω m ) with CFHTLenS data (Liu et al 2015a), CFHT Stripe-82 data (Liu et al 2015b), and DES Science Verification data (Kacprzak et al 2016). Euclid will observe approximately 15 000 deg 2 of the extragalactic sky, an area about two orders of magnitude larger than CFHTLenS and the currently available DES SV data.…”
Section: Introductionmentioning
confidence: 99%